1998
DOI: 10.1002/(sici)1097-0142(19980801)83:3<457::aid-cncr14>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment of patients with maxillary sinus carcinoma

Abstract: BACKGROUND Information regarding results of treatment and possible prognostic factors in patients with maxillary sinus carcinoma is limited. METHODS Between 1969‐1995, 48 consecutive patients presented to the study department for curative treatment of maxillary sinus carcinoma. Tumor classification according to the American Joint Committee on Cancer staging system was T1 in 1 patient, T2 in 6 patients, T3 in 17 patients, and T4 in 24 patients. The N classification was NO in 43 patients, N2a in 1 patient, N2b i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 21 publications
4
65
2
1
Order By: Relevance
“…The close relation between survival and local control underscores the fact that the prognosis for patients with nasal and paranasal sinus carcinoma is related directly to local control of the disease. 4,5,103,117,154,157,174,186,196 In the literature, global results, most often expressed in terms of crude survival, vary between 10% 60,61,63,70,77,80,82,152 and 75%, 40,106,109,132,135,160,161,165,176 with better results in carefully selected patients, in patients with primary tumors of the nasal cavity, and in more recently published articles. The average over- all survival rate from the systematic review analysis was 41%, and the overall survival rate for the 1990s was 51%.…”
Section: Overall Resultsmentioning
confidence: 99%
“…The close relation between survival and local control underscores the fact that the prognosis for patients with nasal and paranasal sinus carcinoma is related directly to local control of the disease. 4,5,103,117,154,157,174,186,196 In the literature, global results, most often expressed in terms of crude survival, vary between 10% 60,61,63,70,77,80,82,152 and 75%, 40,106,109,132,135,160,161,165,176 with better results in carefully selected patients, in patients with primary tumors of the nasal cavity, and in more recently published articles. The average over- all survival rate from the systematic review analysis was 41%, and the overall survival rate for the 1990s was 51%.…”
Section: Overall Resultsmentioning
confidence: 99%
“…Daly et al treated less than one quarter of patients with ENI and also found no nodal relapses [20]. However, Paulino et al and Hoppe et al found a 29 % regional relapse in patients not receiving ENI [13,16]. Le et al found a 12 % regional relapse in patients not receiving ENI, but no nodal relapse in patients receiving ENI [18] there is concern for added RT toxicity [16].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the location of SNCs relative to critical structures, escalating dose to a therapeutic level while limiting treatment-related toxicities has posed a challenge. Prior to the 3D-CRT era, patients were treated with conventional two-dimensional RT (2D-RT) and the prescription dose was typically limited to a median dose of 60-68 Gy (range, 39 Gy-77.2 Gy) [5,8,[11][12][13]18]. LC rates were poor, and serious ophthalmic toxicity occurred in up to 69 % of patients [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations